Pembredelan Majalah Tempo Pada Masa Orde Baru - Rosyada, Nuresa Febriasti; Putra, Arif Permana; Nurhasanah, Ana (Prabayaksa: Journal of History Education, 2022)
The purpose of this study discusses the distribution of Tempo Magazine during the New Order period in 1994. Methods in this study use historical methods, including: heuristic, source criticism, interpretation, and historiography. The results showed that the condition of the press before 1994 was an era of openness heralded by President Suharto in the introductory speech of the 46th Anniversary of the Republic of Indonesia on August 16, 1991, almost all mass media seemed passionate in covering or voicing facts in the community. Tempo magazine is informative and articulate presenting news of the Minister of Finance (Mar'ie Muhammad) with the Minister of Research and Technology (B.J Habibie). Conflict over the purchase of 39 former warships belonging to East Germany for USD 319 million which was severely damaged. As a result of the news, President Suharto made a strong threat to Tempo. The government issued Decree No. 123/ KEP / MENPEN / 1994 as a decree on the release of Tempo magazine. The impact of the release of Tempo magazine in 1994, emerged an act of solidarity from the womb of the press industry born the Organization of the Indonesian Journalists Alliance (AJI) on August 7, 1994.